Re‐Doped p ‐Type Thermoelectric SnSe Polycrystals with Enhanced Power Factor and High ZT > 2 - Su, Bin; Han, Zhanran; Jiang, Yilin; Zhuang, Hua‐Lu; Yu, Jincheng; Pei, Jun; Hu, Haihua; Li, Jing‐Wei; He, Yu‐Xiao; Zhang, Bo‐Ping; Li, Jing‐Feng (Advanced functional materials, 2023)
Thermoelectric technology enables the direct interconversion between heat and electricity. SnSe has received increasing interest as a new promising thermoelectric compound due to its exceptionally high performance reported in crystals. SnSe possesses intrinsic low thermal conductivity as a congenital advantage for thermoelectric, but high thermoelectric performance can be hardly achieved due to the difficulty to realize efficient doping to raise its low carrier concentration to an optimal level. In this work, it is found that a series of rare earth elements are effective dopants for SnSe, which can greatly improve the electrical transport properties of p ‐type polycrystalline SnSe. In particular, the remarkable enhancement in electrical conductivity and power factor is achieved by Na/Er co‐doping at 873 K. The lattice thermal conductivity is reduced due to the presence of abundant defects (dislocations, stacking faults, and twin boundaries). Consequently, a peak thermoelectric figure of merit ZT (2.1) as well as a high average ZT (0.77) are achieved in polycrystalline SnSe.